Ejection of Double Knots from the Radio Core of PKS 1510–089 during the Strong Gamma-Ray Flares in 2015 - Park, Jongho; Lee, Sang-Sung; Kim, Jae-Young; Hodgson, Jeffrey A.; Trippe, Sascha; Kim, Dae-Won; Algaba, Juan Carlos; Kino, Motoki; Zhao, Guang-Yao; Lee, Jee Won; Gurwell, Mark A. (IOP Publishing, 2019)
PKS 1510-089 is a bright and active γ-ray source that showed strong and complex γ-ray flares in mid-2015 during which the Major Atmospheric Gamma Imaging Cerenkov telescopes detected variable very high energy (photon energies >100 GeV) emission. We present long-term multifrequency radio, optical, and γ-ray light curves of PKS 1510-089 from 2013 to 2018, and results of an analysis of the jet kinematics and linear polarization using 43 GHz Very Long Baseline Array data observed between late 2015 and mid-2017. We find that a strong radio flare trails the γ-ray flares in 2015, showing an optically thick spectrum at the beginning and becoming optically thin over time. Two laterally separated knots of emission are observed to emerge from the radio core nearly simultaneously during the γ-ray flares. We detect an edge-brightened linear polarization near the core in the active jet state in 2016, similar to the quiescent jet state in 2008-2013. These observations indicate that the γ-ray flares may originate from compression of the knots by a standing shock in the core and the jet might consist of multiple complex layers showing time-dependent behavior, rather than of a simple structure of a fast jet spine and a slow jet sheath. © 2019. The American Astronomical Society. All rights reserved.